'Smart packet' for energy optimisation in wireless sensor networks. (2017) - Viswanathan, Vijayaragavan; Mahalakshmi, V.J.; Narayanan, Ram Prasadh
Performance of WSNs depends mainly on the network life time. It is obvious that optimising battery power consumption will result in an increased WSN performance. This research work addresses two key factors which influence the energy consumption of a mote. First, analyse the correlation of link quality indicator (LQI) values to the packet delivery ratio (PDR) based on various environmental conditions; second, an empirical analysis of battery consumption under various RF transmission scenarios, such as listening, transmission, reception, multi-hop mode (receive and transmit), idle mode, etc. The experimental results identified various performance issues which arise due to: deployment and battery discharge characteristics of sensor mote in a multi hop network. Through this work, a novel methodology called as 'sleeping pill' protocol is proposed. The proposed protocol resulted in 4% reduction of energy consumption for transmitting 10, 000 packets at −25 dBm transmission power. The same methodology was applied to the multi-hop multipath routing protocol which increased the life time of the network to about 60%. This work was carried out specifically to ascertain the credibility of the 'sleeping pill' protocol on WSNs.